Pengaruh Resiko, Motivasi dan Pengetahuan Investasi terhadap Minat Investasi di Pasar Modal pada Perusahaan PT. Indonex Bangun Investama - Desak Made Kelaci Puspita Putri; Komang Asri Pratiwi; Wisnu Ardiansyah (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
The capital market has become a cornerstone of modern economies, facilitating the flow of funds between investors and business entities to support growth and innovation. However, interest in investing in the Indonesian capital market still faces significant challenges, particularly in terms of risk understanding, perception, and individual motivation for investment. This research aims to explore the factors influencing individual investment interest in PT. Indonex Bangun Investama, a key player in the Indonesian capital market. The research adopts a quantitative approach involving 82 active investors of PT. Indonex Bangun Investama. Data analysis utilizes various statistical techniques such as normality tests, multicollinearity tests, and multiple linear regression analysis to examine the impact of risk, motivation, and investment knowledge variables on investment interest. The analysis results indicate that risk and motivation significantly affect investment interest, while investment knowledge, although important, does not significantly influence investment interest individually. These findings provide deeper insights into the psychological and economic factors underlying individual investment decisions in the Indonesian capital market. The implications of this research suggest the need for a more holistic and strategic educational approach to enhance financial literacy and effective risk mitigation in individual investment strategies. Thus, this research makes a significant contribution to the development of education strategies and risk management in the Indonesian capital market context, laying a foundation for further discussions on expanding accessibility and participation in investment among the public.